Stress-mediated root microbiome shifts and the ‘cry for help’ response in banana (Musa spp.) - V. Swetha; M. Kavino; S. Nakkeeran; S. Marimuthu; R. Raghu (Physiological and Molecular Plant Pathology, 2026)

Solar tree-shaped renewable energy storage system with lightning protection - K.Harinath Reddy; Pujari Harish Kumar; N Chinna Alluraiah; Reshma Gopi R; Ramesh P; Swetha Shekarappa G (Next Research, 2026)

Copepod communities and trophic guilds: Patterns of structuring in tropical coastal waters off Southwest India - R. Amala Swetha; N.V. Madhu; Sudheesh Praveena; K.R. Muraleedharan; P.P. Hafish Mohammed; E. Jithin Prasad; K.S. Arya (Estuarine, Coastal and Shelf Science, 2026)

Talaromyces atroroseus pigment-derived silver nanoparticles functionalized with 6-benzylaminopurine for enhanced in vitro growth of Musa acuminata cv. ‘Grand Nain’ - Kavyarathna; R. Aakash; M. Nithin Kumar; K.U. Minchitha; S. Swetha; Sandeep Suryan; G.S. Nagananda (Biocatalysis and Agricultural Biotechnology, 2026)

An epigenetic switch in vascular phenotype augments anti-tumor immunity - Dae Joong Kim; Mitchell McGinty; Swetha Anandh; Caroline Riedstra; Yuvraj Sethi; Melanie R. Rutkowski; Andrew C. Dudley (Angiogenesis, 2026)
The abnormal tumor vasculature can present a barrier to the infiltration of anti-tumor immune cells, which impairs immune surveillance and response to immunotherapy. Here, we show that genetically deleting the epigenetic factor DNA methyltransferase 1 ( Dnmt1 ) in endothelial cells (ECs) reduces angiogenesis while imparting profound changes to the tumor immune microenvironment (TIME), including increased proportions of CD4 + memory T cells and NK cells. Depleting CD4 + T cells, or blocking lymphocyte egress from the lymph nodes, rescues tumor growth in mice with conditional deletion of Dnmt1 in ECs ( Dnmt1 iECKO ) and dramatically shortens overall survival, whereas NK cells are dispensable. Tumors implanted in Dnmt1 iECKO mice show reduced vascular branching, elevated expression of VCAM1, increased vessel-associated T cells, and a shift in vascular specification, including increased proportions of immune-permissive post-capillary venules (PCVs) and interferon-stimulated ECs (IFN-ECs). Deleting Dnmt1 in EC cultures strikingly potentiates responses to combinations of IFNγ and TNFα and, notably, up-regulates important T-cell co-stimulatory molecules for memory CD4 + T cells, including Icosl , Cd40 , and Tnfsf4 . Finally, immune checkpoint blockade (ICB) administered to Dnmt1 iECKO mice with experimental melanoma lung metastasis reduces tumor burden, with some mice showing tumor eradication. Our findings identify endothelial Dnmt1 as a key regulator of vascular-mediated anti-tumor immunity, providing a rationale for integrating epigenetic modulation of the vasculature with cancer immunotherapy regimens.

Early Detection of Potato Leaf Diseases with PotatoNet-X: A Deep Learning Model Combining ResNet, DenseNet, and Attention Mechanisms - Umesh Kumar Lilhore; P. Kavitha; Swetha G.; Sunder R.; Sarita Simaiya; Ehab Seif Ghith; Shimaa A. Hussien (Potato Research, 2026)

Plant responses to full moonlight requires the SUVH4 HMTase which may target active genes via interaction with the splicing factor SAP18 - Jeevan R. Singiri; Naveen-Kumar Yarra; Sasank Sannidhi; Govindegowda Priyanka; Bupur Swetha; Nurit Novoplansky; Zachor Adler-Agmon; Gideon Grafi (Plant Science, 2026)

Emerging contaminants in urban Soils: Characterization, sources, and environmental impacts of microplastics in southern India - M. Bhuvaneswari; V. Gopal; R. Vinoth; R. Aakash; N.M. Swetha; S. Vinoth kumar; R.R. Krishnamurthy; M.Suresh Gandhi; Renuka Sharma; Ramamoorthy Ayyamperumal (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Identifying plastic pollution hotspots of Vembanad lake, Kerala, India: an integrated approach using artificial intelligence and spatial analysis - P. P. Ayana; M. R. Sethu; Antony Nirmal; M. K. Swetha; V. P. Limna Mol (Wetlands Ecology and Management, 2025)

Long-term trends in heavy metal contamination of marine sediments in the Arabian Gulf: A meta-analysis - S. Swetha; S. Veerasingam; S. Rajendran; Hassan Hassan; Muhammad Zia U. R. Rahman Hashmi; Hamood Alsaadi; Nelson Rangel-Buitrago; Fadhil N. Sadooni (Environmental Monitoring and Assessment, 2025)
Heavy metal (HM) contamination in marine sediments is a critical environmental concern due to its potential ecological and human health impacts. This study provides a comprehensive assessment of the spatial and temporal evolution of HM contamination in Arabian Gulf sediments over a 33-year period (1991–2024). Contamination levels were evaluated using key sediment quality indices such as the contamination factor (CF), geoaccumulation index (I g ₑₒ), pollution load index (PLI), and ecological risk index (ERI) based on available meta-data. Spatial analysis revealed that marine sediments along the Iranian and Saudi Arabian coasts exhibited higher contamination levels compared to those of other Gulf countries. This elevated contamination is likely attributed to industrial discharges, oil spills and effluent releases from desalination plants. Arsenic (As), cadmium (Cd), copper (Cu), nickel (Ni), and lead (Pb) emerged as the primary toxic contributors to sediment pollution. Overall, HM contamination status in the region is predominantly low to moderate, with localized hotspots near industrialized coastal zones. The study highlights the need for scientifically informed waste management strategies to mitigate HM contamination, particularly in nearshore environments impacted by industrial activities. Furthermore, it recommends the implementation of continuous monitoring programs to track temporal trends and identify emerging contamination sources. These findings provide critical insights for environmental managers and policymakers in developing sustainable pollution mitigation frameworks and enhancing the resilience of marine ecosystems in the Arabian Gulf.

Ingestion of weathered high density polyethylene microplastics-induced oxidative stress and modulation of antioxidant responses in post larval stages of Litopenaeus vannamei - M. Leela; V. Pushpalatha; S. Swetha; S. Anusuya; S. Madhavan; S. Eswari; H. Thilagam; R. Thiagarajan; R. Krishnamurthy (Frontiers in Marine Science, 2025)

Microbial lipopeptides: their pharmaceutical and biotechnological potential, applications, and way forward - K. P. Sreelakshmi; M. Madhuri; R. Swetha; Vivek Rangarajan; Utpal Roy (World Journal of Microbiology and Biotechnology, 2024)

Evaluating performance of vortex-diode based hydrodynamic cavitation device scale and pressure drop using coumarin dosimetry - Varaha P. Sarvothaman; Shekhar R. Kulkarni; Janardhanraj Subburaj; Swetha L. Hariharan; Vijay K. Velisoju; Pedro Castaño; Paolo Guida; Deoras M. Prabhudharwadkar; William L. Roberts (Chemical Engineering Journal, 2024)

Rothia santali sp. nov., endophytic bacteria isolated from sandalwood (Santalum album L.) seedling - Ngangyola Tuikhar; Kiran Kirdat; Gayatri Nair; S. Padma; Vipool Thorat; P. Swetha; Shivaji Sathe; R. Sundararaj; Amit Yadav (Archives of Microbiology, 2022)

Extreme drought alters progeny dispersal unit properties of winter wild oat (Avena sterilis L.) - Buzi Raviv; Janardan Khadka; Bupur Swetha; Jeevan R. Singiri; Rohith Grandhi; Eliyahu Shapira; Nurit Novoplansky; Yitzchak Gutterman; Ivan Galis; Marcelo Sternberg; Gideon Grafi (Planta, 2020)

Treatment of fluoride-contaminated water. A review - P. Senthil Kumar; S. Suganya; S. Srinivas; S. Priyadharshini; M. Karthika; R. Karishma Sri; V. Swetha; Mu. Naushad; Eric Lichtfouse (Environmental Chemistry Letters, 2019)

Aseptic Culture Establishment Using Antibiotics with Reference to Their Efficiency and Phytotoxicity in Difficult-to-Establish Native Ney Poovan Banana (Musa, AB) - Pooja Bohra; Ajit Arun Waman; B. N. Sathyanarayana; K. Umesha; S. R. Anu; H. G. Swetha; R. K. Gourish (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

The 18S rDNA gene discriminates between red-listed and unexplored ethnomedicinal species of Myristicaceae restricted to humid tropics of India - T. E. Sheeja; O. B. Rosana; V. P. Swetha; R. S. Shalini; S. Siju; R. Dhanya; P. R. Rahul; B. Krishnamoorthy (Genetic Resources and Crop Evolution, 2014)